IMPLEMENTASI PASAL 54 NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA TERKAIT PELAKSANAAN REHABILITASI TERHADAP PENYALAHGUNA NARKOTIKA DI KABUPATEN BULELENG - Kiha, Prisella Santji Anatji; ardhya, si ngurah; landrawan, i wayan (Universitas Pendidikan Ganesha, 2024)
This research aims to (1) determine the implementation of Article 54 of Law Number 35 of 2009 concerning Narcotics Regarding the Implementation of Rehabilitation for Narcotics Abusers in Buleleng Regency, and (2) determine the obstacles faced by the Buleleng BNNK in implementing rehabilitation for Narcotics abusers in Buleleng National Narcotics Agency. The type of research used is empirical legal research, with a descriptive nature. The research location was carried out at the National Narcotics Agency, Buleleng Regency. The data collection techniques used were observation, interviews and document study. The sampling technique used is the Non Probability Sampling technique. Qualitative data processing and analysis techniques. The results of the research show that (1) the implementation of Article 54 of Law Number 35 of 2009 concerning Narcotics regarding the implementation of rehabilitation for Narcotics abusers at the Buleleng BNNK has not been fully implemented at the Buleleng BNNK, (2) The obstacles faced by the Buleleng BNNK in carrying out rehabilitation are Lack of public knowledge about the existence of the Narcotics Law regarding rehabilitation, narcotics abusers are not yet fully aware, the public's unwillingness to report families who are indicated to be using narcotics and a lack of health workers at the Buleleng BNNK Pratama Clinic.